Media Effect to Risk Perception and Protective Behavior During COVID-19 in Indonesia Partial Least Squares Modeling Analysis - A'yunin, Elia Nur; Arumsari, Imas; Suraya , Izza; Sari, Mega Puspa (Faculty of Public Health, Hasanuddin University, Makassar, 2023)
Indonesia has implemented a Large-Scale Social Distancing policy, limiting major public activities to control the COVID-19 pandemic. This study investigates the media content information, the perception of its role, and its contribution to forming the general public’s risk perception and protective behavior during this situation. This study was an observational study using a cross-sectional design. Data was collected through an online semi-structured questionnaire using Google Forms. A total of 522 participants were obtained through snowball sampling for two weeks. The data analyzed used the Partial Least Squares (PLS) technique. The results showed the structural model of media content information and the perception of media’s role in influencing risk perception and protective behavior. Media content information and perception of media’s role directly influence protective behavior significantly. The only perception of the media’s role is that it significantly influences risk perception. Then, risk perception directly influences protective behavior. The structural model of media content information and perception of media’s role in influencing risk perception and protective behavior during COVID-19 when the transition period to the new normal era in Indonesia has been conducted.